DEVELOPING AND VALIDATING A STABILITY-INDICATING UV-VIS NANODROP 2000C METHOD FOR THE SIMULTANEOUS DETERMINATION OF THE ANTI-HYPERTENSIVE DRUG HYDROCHLOROTHIAZIDE (HCTZ) IN BOTH BULK AND TABLET DOSAGE FORMS - Qasim, Faroq O.; Hami , Mohammed A.; Yousif , Nzar I. (Science Journal of University of Zakho, 2024)
For the simultaneous determination of anti-hypertensive drugs Hydrochlorothiazide (HCTZ) in bulk and tablet dosage forms, a simple, specific, accurate, and precise stability-indicating UV-Vis Nanodrop 2000c method was developed and validated. The maximum absorption of Hydrochlorothiazide was revealed at 271 nm using methanol as a solvent. The validation results showed good linearity (R2 = 0.9997) within the concentration range of 10-50µg/mL. The RSD revealed an acceptable value (less than 0.6 percent) in the precision study at three levels. 1.01 and 3.3g µg/mL were found to represent the LOD and LOQ, respectively. Locally and commercial tablets are Available Drug Products. Accuracy at three levels showed good recovery, more than 99% percent. The proposed method was used to analyse the stability of local and commercial tablets. The stability of their pharmaceuticals was investigated under acidic, oxidative, thermal, alkaline, and photolytic conditions in this research. In accordance with the guidelines set by the International Council for Harmonisation (ICH), the method was effectively validated. Subsequently, the validated method was employed to analyze commercially available pharmaceutical dosage forms.
Keywords: UV-Vis Nanodrop 2000c; Validation; Hydrochlorothiazide; Stability Indicating; Hypertension